PENINGKATAN KANDUNGAN PROTEIN ABON NANGKA MUDA - Harimbi Setyawati, Annastasiya Bou Panawar Purba, Dwi Ana Anggorowati (Jurnal Teknik Kimia, 2012)
Lack of protein content in young jackfruit as shredded raw materials motivated us to do a fermentation process, with the aim of increasing the protein content so that it can become suitable for consumption with 25.398% protein content, which equals that of shredded beef. The existing shredded young jackfruit has protein levels ranging from 15%. In the fermentation process, tempeh yeast and tape yeast are added. Yeast inoculum dose is added as much as 0.5 gr/200 gr for 4 days. Fermentation process treatment for 4 days can increase the protein content from 5.506% to 9.361% with tempeh yeast, and there is 10.591% increase with tape yeast. The best levels of protein from fermentation are used for the manufacture of shredded young jackfruit with the addition of spices, and then fried with frying times: 30, 35, 40, 45, and 50 minutes. From this research the best results were obtained: 40 minutes frying time, 25.398% protein content, fat content of 26.972%, 28.294% carbohydrate, water content of 5.731%, and negative Ecoli bacteria. Key words:  shredded, fermentation, protein enhancement, young jackfruit.